Reading Taboos as Allegory in O. V. Vijayan’s The Saga of Dharmapuri - Singh, Ravindra Pratap (Journal of Applied Cultural Studies, 2015)
The Saga of Dharmapuri, written during the days of political Emergency in India, and published when the emergency was lifted, is a poignant satire upon the then Indian political administration. The decoders of this allegory find Dharmapuri in parallel with Delhi, and that of the King with Jawahar Lal Nehru, the first Prime Minister of India. The beginning of the novel with the visible apocalypse of etiquette and decency in public mannerism, connotes its leanings towards postmodernist announcement of the end of grand tradition, and making even taboos to work as allegory in formal discourse. The present paper is an attempt towards decoding different metaphors and allegories used in The Saga of Dharmapuri.